Self-assessment on the achievement of the ability of mathematical proportional application in Meaningful Instructional Design (MID) learning viewed from student’s learning style - Mulyono, Mulyono; Kartono, Kartono; Rosyida, Meis Dania Nila (Department of Mathematics, Universitas Negeri Semarang, 2018)
This study aims to (1) test the students' mathematical proportional reasoning ability to achieve classical mastery, (2) to analyze the average achievement of mathematical proportional reasoning ability in Meaningful Instructional Design learning by applying self-assessment with the common learning model (3) to test the proportion of students’ mastery in Meaningful Instructional Design learning by applying self-assessment which is better than the proportion of the common learning model and (4) to obtain a description of students' proportional reasoning abilities of visual, auditory, and kinesthetic style of learning style. The method used in this research is Mixed Methods Concurrent Embedded Design. The quantitative subject of this study is the students of class VIII B MTs NU Banat Kudus as the experimental class which use Meaningful Instructional Design, while the subject of qualitative research is 6 students of class VIII B consisting of 2 students with the high and low value on mathematical proportional reasoning test in each learning style group. Eventually, the results of this study are (1) the achievement of students’ mathematical proportional reasoning ability is significant in MID learning, (2) there is difference of proportional reasoning ability in MID learning model with a common used learning model, (3) the proportion of students' learning mastery by using Meaningful Instructional Design model with Self-assessment is higher than those who use the common learning model and (4) the students with visual learning style are able to propose and perform mathematical manipulation by understanding and remembering the material ever seen and written, the students with auditory learning style are able to make guesses, present mathematical manipulations, and draw conclusions by understanding and remembering material discussed, while students with kinesthetic learning style are able to make guesses, perform mathematical manipulations, and draw conclusions by understanding and remembering material which is ever practiced.